Echocardiographic and Biochemical Factors Predicting Arrhythmia Recurrence After Catheter Ablation of Atrial Fibrillation—An Observational Study - Charitakis, Emmanouil; Karlsson, Lars O.; Papageorgiou, Joanna-Maria; Walfridsson, Ulla; Carlhäll, Carl-Johan (Frontiers in Physiology, 2019)
Background: RFA is a well-established treatment for symptomatic patients with AF. However, the success rate of a single procedure is low. We aimed to investigate the association between the risk of recurrence of atrial fibrillation (AF) after a single radiofrequency ablation (RFA) procedure and cardiac neurohormonal function, left atrial (LA) mechanical function as well as proteins related to inflammation, fibrosis and apoptosis. Methods and Results: We studied 189 patients undergoing RFA between January 2012 and April 2014, with a follow-up period of 12 months. A logistic regression analysis was performed to investigate the association between pre-ablation LA emptying fraction (LAEF), MR-proANP, Caspase-8 (CASP8), Neurotrophin-3 (NT3), and the risk for recurrence of AF after a single RFA procedure. 119 (63.0 %) patients had a recurrence during a mean follow-up of 402±73 days. An increased risk of recurrence was associated with: Elevated MR-proANP (fourth quartile vs. first quartile: HR, 2.80 (95% CI, 1.14-6.90]; P=0.025); Low LAEF (fourth quartile vs. first quartile: hazard ratio [HR], 2.41 [95% CI, 1.01-5.79]; P=0.045); Elevated CASP8 (fourth quartile vs. first quartile: HR 12.198 95% CI 2.216-67.129; P=0.004); Elevated NT-3 (fourth quartile vs. first quartile: HR 7.485 95% CI 1.353-41.402; P=0.021). In a receiver operating characteristic curve analysis, the combination of MR-proANP, CASP8 and NT3 produced an area under the curve of 0.819; CI 95% (0.710-0.928). Conclusions: Patients with better LA mechanical function and lower levels of atrial neurohormones as well as of proteins related to fibrosis and apoptosis, have a better outcome after an RFA procedure.